Pelatihan Pencatatan Keuangan Harian Dan Biaya Lingkungan Untuk Umkm Pemula Di Palembang - Ruth Samantha Hamzah; Arista Hakiki; Patmawati; Muhammad Prans Panca Renta; Riska Tharika; Efva Octavina Donata Gozali; Mutiara Lusiana Annisa (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Informatika Indonesia Surabaya, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of the economy, but start-up MSMEs in Palembang City still face fundamental obstacles in terms of financial recording and managing the environmental impact of their businesses. The main problems identified include the lack of a proper financial recording system, the mixing of business and personal finances, and the absence of documentation of environmental costs such as energy use and waste. This community service activity aims to address these issues through three integrated solutions: training in simple daily financial recording, training in the application of Microsoft Excel as a recording technology, and education and simulation of environmental cost recording. The implementation method involves 20 start-up MSME partners in the food and beverage sector through the stages of preparation, training, direct assistance, and evaluation. The technology applied is a ready-to-use Microsoft Excel template that includes daily recording, cash flow, profit and loss, cost of production, and environmental costs. The targeted outputs of this program are an increase in participants' financial and environmental administration capabilities, the development of locally-based training modules, the implementation of an environmentally-friendly recording system in business units, and scientific publications. This program is expected to promote operational efficiency and business sustainability for start-up MSMEs.